Pemberdayaan Petani dengan Teknologi Reaktor Pirolisis Biohayati Sekam Padi di Lahan Gambut Desa Ganesha Mukti, Banyuasin: pemberdayaan sekam padi di lahan gambut - Lumbantoruan, Santa; Harsana, Primayoga; Ramadhani, Fitri; Cahya, Muhardianto; Habibulloh (Universitas Mataram, 2025)
Ganesha Mukti Village, located in Banyuasin Regency, is a peatland-based agricultural area facing challenges such as low soil fertility and high acidity. This community service initiative aims to empower farmers through the application of a bio-pyrolysis reactor using rice husks as feedstock, offering a solution for agricultural waste management and soil quality improvement. Activities included focus group discussions (FGDs), technical training, equipment demonstrations, and participatory evaluations. Results showed a significant increase in farmers’ understanding—from 30–60% (pre-test) to 80–85% (post-test)—and 77.5% of participants expressed readiness to operate the technology independently.The bio-pyrolysis reactor produces two main outputs: biochar and liquid smoke, both of which serve as soil ameliorants and environmentally friendly inputs for peatland farming. Laboratory analysis revealed that biochar contains substantial macronutrients—nitrogen (0.74–0.91%), phosphorus (0.129–0.174%), and potassium (0.76–0.87%)—comparable to conventional organic fertilizers and chemically more stable, thus enhancing peat soil fertility. Meanwhile, the liquid smoke contains nitrogen (0.16%), phosphorus (0.057%), and potassium (0.001%), which, although low, still contributes as a supplementary nutrient source and functions as a botanical pesticide and eco-friendly pest control agent.The synergy between rice husk-derived biochar and liquid smoke is considered effective in boosting agricultural productivity, reducing dependence on inorganic inputs, and supporting sustainable farming systems on peatlands.